The Effect of Defensive Exercises in the Motor Response to Develop Some Defensive Skills for Young Basketball Players - Noor Alhuda Satar Jabar; Huda Shihab Jari (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of physical and skill abilities in basketball has increased in recent times because modernplay has increased in difficulty and complexity compared to previous playing styles, and the motor abilitiesand the kinetic response are of fundamental importance in building and advancing the basketball player andworks to improve the player’s level of skill and planning, and the speed of timely decision-making and thespeed of the movement’s reaction to the player, and understanding this relationship is the basis for developingappropriate training curricula that help us reach high sports levels, so it became based on the above, theimportance of research is reflected in the necessity of numbers of curricula and training programs. As forthe most important conclusions, they were: The success of the training program in developing the defensiveskills of the experimental group and that the training program had a noticeable effect on the performance ofthe players by comparing the results of the post-test of the control and experimental groups and confirmingthat the special exercises had a positive effect in developing the defensive skills of basketball.